2022
DOI: 10.2147/idr.s381730
|View full text |Cite
|
Sign up to set email alerts
|

Rare Hepatic Cryptococcosis Mimicked Metastatic Liver Cancer and Confirmed by Metagenomic Next-Generation Sequencing in an Immunocompetent Patient: A Case Report

Abstract: Background Cryptococcus neoformans ( C. neoformans) is commonly presented in immunocompromised individuals and causes cryptococcosis mostly in the respiratory and/or central nervous system. Liver cryptococcosis is exceedingly rare and sometimes difficult to diagnose through conventional assays. Case Presentation The present study reports a rare case of liver cryptococcosis characterized by increased serum carbohydrate antigen 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the potential utility of mNGS for detecting Cryptococcus in the central nervous system, the pulmonary system, and the liver. [4][5][6] Yet, few studies have focused on using the method in differentiating between an IRIS and a relapse of cryptococcal meningitis. This study reports the use of mNGS to aid in diagnosing recurrent cryptococcal meningitis in a person living with HIV experiencing recurring symptoms, despite negative culture results for Cryptococcus neoformans in the cerebrospinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the potential utility of mNGS for detecting Cryptococcus in the central nervous system, the pulmonary system, and the liver. [4][5][6] Yet, few studies have focused on using the method in differentiating between an IRIS and a relapse of cryptococcal meningitis. This study reports the use of mNGS to aid in diagnosing recurrent cryptococcal meningitis in a person living with HIV experiencing recurring symptoms, despite negative culture results for Cryptococcus neoformans in the cerebrospinal fluid.…”
Section: Introductionmentioning
confidence: 99%